BENCHMARKING AS A TOOL OF AGRICULTURAL ENTERPRISES MARKETING ACTIVITY - Славіна, Н. А.; Лаврук, О. С. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
One of the most effective tools; that gives the opportunity to company continuously to increase productivity; to improve the quality of their activities precede competitors is technology benchmarking The research was based on process analysis and synthesis methods; scientific abstraction method - for “benchmarking” meaning definition; historical and logical approach - to represent the benchmarking evolution and to identify factors driving force in this process; analogies method - to assess the marketing activity trends of national enterprises. It was observed the features of the benchmarking usage as a marketing tool and identified opportunities for its implementation in agricultural enterprises. We made focus on the major problems of implementing the benchmarking activities main elements in agricultural enterprises and their impact on marketing effectiveness activity; using foreign experience It was demonstrated; that benchmarking can help to understand; how the best enterprises work; to achieve their levels; to get much better results by reducing costs; increasing productivity; optimizing the company strategic direction; which is especially important for the entire agricultural field.